Experimental model of heterotopic ossification in Wistar rats - Zotz,T.G.G. (2012)
Heterotopic ossification (HO) is a metaplastic biological process in which there is newly formed bone in soft tissues adjacent to large joints, resulting in joint mobility deficit. In order to determine which treatment techniques are more appropriate for such condition, experimental models of induced heterotopic bone formation have been proposed using heterologous demineralized bone matrix implants and bone morphogenetic protein and other tissues. The objective of the present experimental study was to identify a reliable protocol to induce HO in Wistar rats, based on autologous bone marrow (BM) implantation, comparing 3 different BM volumes and based on literature evidence of this HO induction model in larger laboratory animals. Twelve male Wistar albino rats weighing 350/390 g were used. The animals were anesthetized for blood sampling before HO induction in order to quantify serum alkaline phosphatase (ALP). HO was induced by BM implantation in both quadriceps muscles of these animals, experimental group (EG). Thirty-five days after the induction, another blood sample was collected for ALP determination. The results showed a weight gain in the EG and no significant difference in ALP levels when comparing the periods before and after induction. Qualitative histological analysis confirmed the occurrence of heterotopic ossification in all 12 EG rats. In conclusion, the HO induction model was effective when 0.35 mL autologous BM was applied to the quadriceps of Wistar rats.